Uterine Malignant Mixed Mullerian Tumor: Review of Recent Literature - Zhan, MD, PhD, Haiying; Chen, MD, PhD, Frank; Huang, MD, PhD, Ying (North American Journal of Medicine and Science, 2017)
Uterine Malignant Mixed Mullerian Tumor (MMMT) is an uncommon neoplasm with aggressive clinical course. It shares similar etiology, clinical and pathologic features of high-grade endometrial carcinoma. As such, uterine MMMT has been recently regarded as high grade de-differentiated endometrial carcinoma. Histologically, uterine MMMT is composed of an admixture of malignant epithelial and mesenchymal components. Substantial immunohistochemical and molecular genetic evidence has suggested that these two components share the same cellular origin and the mesenchymal component might derive from the epithelial component via epithelial-mesenchymal transition. This article reviews the recent literature related to the pathogenesis, histopathology, diagnosis, and management of uterine MMMT. [N A J Med Sci. 2017;10(3):110-115. DOI: 10.7156/najms.2017.1003110]